Dual behavior of caustic optical beams facing obstacles - Vaveliuk, Pablo (2017)
A full propagation analysis on both fold-type and cusp-type caustic optical beams under various setups of obstructions is theoretically and experimentally performed. It is demonstrated that the self-healing property of caustic optical beams that include the famous Airy beam is a quite relative property. In fact, fold-type and cusp-type beams cannot only behave as self-healing beams by blocking the main intensity peak, but also behave as self-breaking ones in a nonintuitive manner: by blocking a lateral side of the beam without touching the central intensity peak. The regeneration and rupture processes of caustic beams follow a nonlocal propagation dynamic unlike the other conventional beams. Moreover, deep differences between fold and cusp caustic beams are pointed out once facing certain obstructions. The cusp-caustic beam can be broken down by the obstacle placed in a dark zone outside the caustic region, while the fold-type one remains unaltered. This beam rupture confirms the key role of a hidden propagating field in the shadow region for cusp beams that coexist with the evanescent one. The obtained results cast down the established idea that the Airy beam is a robust self-healing beam since any caustic beam can behave in a dual manner depending on the obstruction location. These facts open up different perspectives for the applications in which the self-healing properties of the beam are relevant.